Phylogeography of Hipposideros armiger (Chiroptera: Hipposideridae) in the Oriental Region: the contribution of multiple Pleistocene glacial refugia and intrinsic factors to contemporary population genetic structure - Ai‐Qing Lin; Gabor Csorba; Lin‐Feng Li; Ting‐Lei Jiang; Guan‐Jun Lu; Vu Dinh Thong; Pipat Soisook; Ke‐Ping Sun; Jiang Feng (Journal of Biogeography, 2014)
Aim The goals of our study were to assess the population history and genetic structure of the widespread bat H ipposideros armiger , and to evaluate the effect of palaeoclimatic changes and dispersal patterns on this species. Location S outh C hina, mainland S outheast A sia and the S outh H imalayas. Methods We amplified two mitochondrial DNA (mt DNA ) regions (cyt b and D ‐loop) and seven nuclear microsatellite loci (n SSR s) from 216 individuals of H . armiger . To examine the evolutionary history of this species, we constructed maximum likelihood and Bayesian phylogenetic trees based on the two mt DNA regions. From the mt DNA and/or n SSR data, we assessed population genetic structure using analysis of molecular variance ( AMOVA ) and median‐joining network and structure analyses. We also estimated demographic history and gene flow using a B ayesian skyline plot and the program I Ma 2. Results Phylogenetic and median‐joining network analyses revealed that H . armiger comprises two distinct mt DNA clades divided into seven subclades. The results of AMOVA suggested strong population genetic structure based on mt DNA , but weak structure based on n SSR s. structure analysis identified three population clusters and also showed weak genetic structure at the nuclear level. Demographic analyses revealed two population expansion events c . 0.62 Ma and c . 0.25 Ma. The basic phylogeographical structure of H . armiger was established by 0.24 Ma. I Ma 2 analysis demonstrated that substantial gene flow has occurred between different regions since then. Additionally, non‐significant population structure and significant gene flow were detected between T aiwan and H ainan island populations and those from mainland C hina. Main conclusions Our results suggest that divergence and population expansion of H . armiger occurred in association with P leistocene climatic changes and that multiple refugia may have existed for this species. Post‐glacial male‐biased dispersal was likely to be the primary contributor to the contemporary genetic structure of H . armiger populations. Gene flow may have contributed greatly to the genetic structure of insular populations and populations from mainland C hina.

Allopatric divergence and phylogeographic structure of the plateau zokor ( Eospalax baileyi ), a fossorial rodent endemic to the Qinghai–Tibetan Plateau - Li‐Zhou Tang; Liu‐Yang Wang; Zhen‐Yuan Cai; Tong‐Zuo Zhang; Hai‐Xin Ci; Gong‐Hua Lin; Jian‐Ping Su; Jian‐Quan Liu (Journal of Biogeography, 2010)
Aim Most species of temperate regions are believed to have shifted to lower latitudes or elevations during the glacial periods of the Quaternary. In this study we test whether this phylogeographic assumption is also true for the plateau zokor ( Eospalax baileyi ), a fossorial rodent endemic to the climate‐sensitive Qinghai–Tibetan Plateau (QTP), which ranges in elevation from 2600 to 4600 m. Location The QTP of western China. Methods Phylogeographic analyses were conducted based on the mitochondrial cytochrome b gene sequences of 193 individuals from 20 populations over the entire range of the species. Results A total of 54 haplotypes identified in the present study clustered into four geographically correlated clades located in the interior of the QTP (clade A) and at the plateau edge (B, C and D). Molecular calibrations suggest that the interior plateau (A) and plateau‐edge (B–D) clades diverged at 1.2 Ma and that the three plateau‐edge clades diverged between 0.85 and 0.80 Ma. These estimates are concordant with diastrophism and glaciation events in the QTP. Coalescent tests rejected both the hypothesis that all current populations originated from a single refugium at a low elevation during the Last Glacial Maximum (LGM) and the hypothesis that the two lineages diverged during the LGM. The tests instead supported the hypothesis that there were four refugia during the LGM, and that the four clades diverged prior to the late Pleistocene. Main conclusions Our results suggest that Quaternary diastrophisms and glaciations repeatedly promoted allopatric divergence of the plateau zokor into geographical clades, and that these regional clades subsequently persisted at high elevations, rather than migrating to the low‐elevation plateau edge during subsequent glacial ages.